2012
DOI: 10.1007/s00217-012-1661-7
|View full text |Cite
|
Sign up to set email alerts
|

Sensorial characteristics of Spanish traditional melon genotypes: has the flavor of melon changed in the last century?

Abstract: Sensory proWling was applied as an eVective tool in melon characterization to evaluate twenty-six melon varieties, landraces and commercial hybrids over 3 years of harvesting. The landraces were from Villaconejos, a Madrilean village historically specialized in melon cultivation. These landraces have remarkable morphological and molecular diversity according to previous studies. Individual panel results related to color, Wrmness, juiciness, sweetness, acidity and Wbrosity, and seven diVerent aromas of melon fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The melon flesh volatile profile has already been deeply studied, basically in commercial genotypes, but also including a few representatives of other horticultural groups [9,[11][12][13][14][15][16][17][18][19][20][21], and the comprehension of the pathways and genes involved in their biosynthesis is currently being prompted using genomic, transcriptomic and biochemical approaches and also segregating populations [22][23][24][25][26][27][28]. Recently, the flesh aroma profile of a melon core collection of 71 accessions representing the whole species diversity has been analyzed [5].…”
Section: Introductionmentioning
confidence: 99%
“…The melon flesh volatile profile has already been deeply studied, basically in commercial genotypes, but also including a few representatives of other horticultural groups [9,[11][12][13][14][15][16][17][18][19][20][21], and the comprehension of the pathways and genes involved in their biosynthesis is currently being prompted using genomic, transcriptomic and biochemical approaches and also segregating populations [22][23][24][25][26][27][28]. Recently, the flesh aroma profile of a melon core collection of 71 accessions representing the whole species diversity has been analyzed [5].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been suggested that the aroma profile is highly genotype dependent, although it also presents an environmental effect . Most studies conducted to date in melon have analyzed some genotypes of commercial interest, mainly representative of the cantaloupe or winter melon market classes, with only a few references including samples of other horticultural groups ( conomon , makuwa and dudaim ) . These previous studies have focused on specific chemical pathways or on the changes in VOC content measured with different methodologies, and under different developmental stages, postharvest conditions or crop management, including fertilization, irrigation and grafting , .…”
Section: Introductionmentioning
confidence: 99%
“…Discriminating melon colors is an important parameter that is often associated with ripeness and plays a key role in consumer perception of food items before purchase. Galia melon is a hybrid originating from a Cantaloupe–Honeydew cross; ripeness is measured not by softness at the stem, but rather by color and fragrance [32]. According to Sánchez et al (2014), Cantaloupe type melons may be harvested, when the external color beneath the netting begins to change from green to yellow-green because the skin color gradually changes light yellow, but the orange-fleshed pulp requires non-destructive methods in order to avoid damage to the fruit at full ripeness [25].…”
Section: Discussionmentioning
confidence: 99%